Heteroaromatization with 4-phenyldiazenyl-1-naphthol. Part III: One-pot synthesis and DFT study of 4H-naphthopyran derivatives - Mohamed, Hany Mostafa; Abd El-Wahab, Ashraf Hassan Fekry; El-Gogary, Tarek Maamon (European Journal of Chemistry, 2017)
A one pot three component reaction of 4-phenyldiazenyl-1-naphthol (1), p-chloro benzaldehyde (2) and malononitrile or ethyl cyanoacetate (3) in ethanol/piperidine under reflux afforded 2-amino-4-(p-chlorophenyl)-6-phenyldiazenyl-4H-naphtho[1,2-b]pyrano-3-carbonitrile (4a) and ethyl 2-amino-4-(p-chlorophenyl)-6-phenyldiazenyl-4H-naphtho[1,2-b]pyrano -3-carboxylate (4b). Structure of these compounds was established on the basis of IR, 1H NMR, 13C NMR, Mass and UV-Vis spectra. Molecular geometry of compounds 4a and b was obtained at B3LYP/6-31+G(d) level. Two tautomers and two conformers were geometrically optimized. The tautomers are separated by about 7.942 kcal/mol while rotational conformers are only separated by 0.511 kcal/mol. Molecular reactivity descriptors including global electrophilicity, hardness, softness and local condensed Fukui functions were computed and discussed. Frontier molecular orbitals (HOMO and LUMO) were also computed.